2018
DOI: 10.1002/brb3.931
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of freezing of gait in Chinese patients with Parkinson's disease

Abstract: Objective: To explore the clinical predictors of freezing of gait (FOG) in Chinese patients with Parkinson's disease (PD). Methods:This study included 225 patients with PD who completed a three-year follow-up visit. The end-point was the presence of FOG (freezers), which was assessed during the follow-up visit. Group comparisons were conducted, followed by a further forward binary logistic regression analysis.Results: Eighty-five patients with PD (38%) had developed FOG at the end of study.At baseline, freeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 35 publications
12
31
0
Order By: Relevance
“…We found FOG in PD to be unrelated to sex and only weakly associated with patient age, consistent with the majority of other prospective studies [ 4 , 8 , 10 12 , 30 ]. On the other hand, supporting extensive literature, we found disease duration to be strongly associated with FOG [ 4 7 , 9 , 12 , 13 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found FOG in PD to be unrelated to sex and only weakly associated with patient age, consistent with the majority of other prospective studies [ 4 , 8 , 10 12 , 30 ]. On the other hand, supporting extensive literature, we found disease duration to be strongly associated with FOG [ 4 7 , 9 , 12 , 13 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…This result suggested that patients with FOG needed more dopaminergic drugs in order to improve motor symptoms and reach a nearly normal life compared with those without FOG. This phenomenon was also observed in other studies in which patients with FOG needed more dopaminergic drugs and were mainly in the advanced stage of PD 21,22. Our data did not find that FOG was associated with the motor severity according to the scores of Hoehn–Yahr stage and UPDRS-Ⅲ.…”
Section: Discussionsupporting
confidence: 83%
“…FOG is a common disabling symptom mainly at the advanced stage of disease and the prevalence has varied from 7% in PD patients with a recent diagnosis to 63% 19,20,21. FOG prevalence reflects a mixed population of patients with early and advanced disease, most of whom could be improved by dopaminergic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence increases with disease duration but clinically it is difficult to predict which patients will transition to develop FOG. A number of factors contribute to FOG risk which include age, anxiety, depression, and severity of motor symptoms but the role of cognition in the development of FOG is still debated in the literature [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%